Acquisition of terrestrial neon during accretion – A mixture of solar wind and planetary components. (1st November 2019) - Vogt, Manfred; Hopp, Jens; Gail, Hans-Peter; Ott, Ulrich; Trieloff, Mario
Abstract: Earth's mantle contains Ne resembling the solar wind implanted Ne-B component in meteorites ( 20 Ne/ 22 NeNe-B : ∼12.7). The atmosphere, instead, displays a "planetary" signature ( 20 Ne/ 22 NeAtm : 9.80). We explore the parameter space of a model that explains these isotopic variations by the contribution of late accreting volatile-rich material (e.g., carbonaceous chondrite-like) to Earth́s atmosphere, while Earth́s mantle incorporated solar wind type Ne that was previously implanted into part of the accreting material. Analyses of the present-day terrestrial influx mass distributions show two major peaks at large bodies >1 km and small ∼200 µm dust particles. The latter dominate the influx of the surface implanted Ne-B component. Ne measurements of small particles define a maximum surface flux (neon reaching the terrestrial surface) peaking at 9 µm, while larger micrometeorites experience ablation losses and isotopic fractionation upon atmospheric entry. Using these data, we reconstruct the unfractionated Ne-B upper atmosphere flux which peaks at ∼75 µm. As the extraterrestrial influx mass distribution between larger bodies and debris dust is governed by equilibrium due to collisions and fragmentation, it is an approximation of the early solar system (after nebula dissipation), where the mass distribution was similar but total fluxes were higher. Contributions of Ne-B by small dust and planetary Ne-A from larger bodies strongly depend on formation region. Originating around the 1 AU region, early accretionary fluxes were dominated by Ne-B as large bodies likely contained only negligible amounts of Ne-A. Ne-B will be ultimately delivered to the earliest protoatmosphere by impact or thermal degassing and a significant fraction of Ne-B can enter the Earth́s interior via dissolution into a magma ocean before the Moon-forming impact. After the Moon-forming impact, Ne-B reenters the atmosphere by mantle degassing and a later meteoritic contribution modified the atmospheric composition. This meteoritic component was likely dominated by Ne-A, as the only remaining planetesimals at that time were in the asteroid belt or beyond, leading to preferential contributions of carbonaceous chondrite-type material. In our model we take into account possible variations of several parameters, e.g. the isotopic composition of the late accretion (i.e., 20 Ne/ 22 Ne: 5.2–9.2). For example, a 20 Ne/ 22 Ne ratio of 8.2 (Ne-A composition) would imply ∼2% mass increase of Earth from CC-type material after the Moon-forming impact, and would require that todaýs atmosphere ( 20 Ne/ 22 Ne = 9.8) formed by roughly equal mixing of late accreted Ne-A and mantle Ne-B. The amount of Ne-B added from the mantle implies a certain degree of mantle degassing (in this case 82–96%, depending on todaýs mantle neon inventory) and constrains two further parameters: the fraction of solar wind irradiated material delivered to Earth before the Moon-forming impact and the magma ocean depth. The latter determines the fraction of Ne-B dissolved from a protoatmosphere. For example, magma ocean depths between 500 and 2900 km allow 4–15% dissolution of the protoatmospheric Ne-B inventory, and would require only less than 10% of irradiated accreting material. Only unreasonable magma ocean depths lower than 200 km require several ten percent of irradiated material.